Reconstruct the Aggressiveness Therapy of Child (Case Study on Ratna Kumara Kindergarten, Medahan Village, Blahbatuh, Gianyar, Bali) - Antara, Putu Aditya (Universitas Negeri Semarang, 2016)
This study aims to determine 1) the form of aggressive therapies developed for children in kindergarten; 2) factors related to the development of aggressive therapies developed for children in kindergarten. This research was conducted in Ratna Kumara Kindergarten, Medahan Village, Blahbatuh, Gianyar, Bali in 2014 with consists of 22 children. This research is a qualitative case study type. Data were collected through observation, interviews and document analysis. The results showed 1) the aggressive form of therapy developed through individual stimulation such as yoga, understand emotions, playing music, singing individual and social stimulation such as creative movement, role play, work of mutual cooperation; 2) the study found several factors that support children's success therapy aggressiveness that teachers have the knowledge and understanding of children's education, can create a joyful learning, shows the close relationship and a good working team of fellow teachers, establish communication and good cooperation with parents, supported with adequate learning facilities and a comfortable environment as well as healthy.